Semiosis and joint student–teacher action. Contract-milieu dialectics in a case study of two subsequent primary school earth science sessions. Issue 7 (3rd May 2022) - Santini, Jérôme; Sensevy, Gérard; Quilio, Serge; Forest, Dominique; Blocher, Jean-Noël
ABSTRACT: This paper addresses the subject of the semiosis process in the transactions between teachers and students about the knowledge at stake in science education. We present a conceptualisation of these transactions as a joint action between students and teachers. This conceptualisation enables us to understand the semiosis process as it unfolds during teaching–learning situations as the semiosis of both the didactic contract and the didactic milieu. We analyse this semiosis in a case study of earth science education at 5th grade, which comprised two subsequent teaching sessions delivered by the same teacher. Our results give an account of the contract–milieu semiosis under the description of different semiotic modes (speech, gestures, stance, gaze, writings, modellings and proxemics). We also define the generic and specific dimensions of semiosis in relation to the knowledge at stake. Finally, we evaluate the relevance of the teaching practice we observed in terms of its staging of a relationship between the semiosis of didactic contracts and didactic milieus.